2019
DOI: 10.1002/mabi.201900122
|View full text |Cite
|
Sign up to set email alerts
|

Redox‐Responsive Resilin‐Like Hydrogels for Tissue Engineering and Drug Delivery Applications

Abstract: Resilin, a protein found in insect cuticles, is renowned for its outstanding elastomeric properties. The authors' laboratory previously developed a recombinant protein, which consisted of consensus resilin‐like repeats from Anopheles gambiae, and demonstrated its potential in cartilage and vascular engineering. To broaden the versatility of the resilin‐like protein, this study utilizes a cleavable crosslinker, which contains a disulfide bond, to develop smart resilin‐like hydrogels that are redox‐responsive. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 55 publications
0
25
0
Order By: Relevance
“… RLP 12 -RGD 2 -MMP-HBD, RLP 12 -RGD, RLP 12 -HBD, RLP 12 -MMP Cell-binding sequence (RGD), matrix metalloproteinase cleavable peptide (MMP), heparin-binding domain (HBD) Increase in cellular adhesion, biodegradation and metabolic activity (with no inflammatory response), and mechanical property Tissue engineering 17 , 63 , 64 REC or RLP 4 -ELP 7 -CLP 2 Elastin-like polypeptide (ELP), collagen-like polypeptide (CLP) Self-assembled network of flexible often aligned fibres (different to that of the twisted rope-helical structure) at physiological temperature Tissue engineering 41 An X -EGFP (where X = 4, 8, 16 and 32) Enhanced green fluorescence protein (EGFP) Autofluorescence. Bioimaging 42 RZ 10 -RGD, RZ 10 -BMP2, RZ 10 -QK Cell-binding sequence (RGD), bone morphogenetic peptide (BMP), vascular endothelial growth factor-mimicking domain (QK) Increase in cellular adhesion and differentiation, and mechanical property Tissue engineering 44 , 67 70 RLP n -SLP n (where n = 1, 4 and 8) Silk-like polypeptide (SLP) Spherical micelle (SLP core) to nanofibril to large coalescence with increase in temperature. Upshift in UCST and stiffness of hydrogel with increase in RLP length.…”
Section: Engineering Structure Composition and Stimuli Responsivenesmentioning
confidence: 99%
See 2 more Smart Citations
“… RLP 12 -RGD 2 -MMP-HBD, RLP 12 -RGD, RLP 12 -HBD, RLP 12 -MMP Cell-binding sequence (RGD), matrix metalloproteinase cleavable peptide (MMP), heparin-binding domain (HBD) Increase in cellular adhesion, biodegradation and metabolic activity (with no inflammatory response), and mechanical property Tissue engineering 17 , 63 , 64 REC or RLP 4 -ELP 7 -CLP 2 Elastin-like polypeptide (ELP), collagen-like polypeptide (CLP) Self-assembled network of flexible often aligned fibres (different to that of the twisted rope-helical structure) at physiological temperature Tissue engineering 41 An X -EGFP (where X = 4, 8, 16 and 32) Enhanced green fluorescence protein (EGFP) Autofluorescence. Bioimaging 42 RZ 10 -RGD, RZ 10 -BMP2, RZ 10 -QK Cell-binding sequence (RGD), bone morphogenetic peptide (BMP), vascular endothelial growth factor-mimicking domain (QK) Increase in cellular adhesion and differentiation, and mechanical property Tissue engineering 44 , 67 70 RLP n -SLP n (where n = 1, 4 and 8) Silk-like polypeptide (SLP) Spherical micelle (SLP core) to nanofibril to large coalescence with increase in temperature. Upshift in UCST and stiffness of hydrogel with increase in RLP length.…”
Section: Engineering Structure Composition and Stimuli Responsivenesmentioning
confidence: 99%
“…Conversely, hydrogels fabricated from RZ 10 -QK showed increased endothelial-specific markers and endothelial function and suggested that protein-engineered microenvironments are sufficient to promote endothelial differentiation in the absence of exogenous growth factors 68 . Recently, RZ 10 -RGD hydrogels were also fabricated using a redox-responsive crosslinker, 3,3′-dithiobis(sulfosuccinimidyl propionate) (DTSSP), which showed excellent NIH-3T3 fibroblast viability and proliferation, and potential in vitro degradation and drug (dextran) delivery applications 70 . However, the modular RLP hydrogels crosslinked with DTSSP exhibited shear storage modulus lower than the hydrogels crosslinked using THP 44 and TGase 69 .…”
Section: Rlp-based Modular Hydrogels: Bioactivity Tuneable Mechanicamentioning
confidence: 99%
See 1 more Smart Citation
“…Taking advantage of the recombinant nature of RLPs, Su et al engineered their novel RZ10-RGD hydrogel to respond to changes in redox [ 395 ]. They used 3,3′-dithiobis(sulfosuccinimidyl propionate) (DTSSP), a redox-responsive crosslinker, to create RLP hydrogels that degrade in a reducing environment ( Fig.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%
“…In non-reducing conditions, release rate decreased with an increase in dextran MW ( Fig. 22 B) [ 395 ]. The redox-responsiveness of this novel hydrogel makes it a promising candidate for tumor-specific drug delivery.…”
Section: Applications In Drug Deliverymentioning
confidence: 99%